2005
DOI: 10.1016/s0002-9440(10)61229-1
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Activates Matrix Metalloproteinase Type II and Mimics Age-Associated Carotid Arterial Remodeling in Young Rats

Abstract: Increased angiotensin II (Ang II), matrix metalloproteinase type II (MMP2), and sympathetic activity accompany age-associated arterial remodeling. To analyze this relationship, we infused a low subpressor dose of Ang II into young (8 months old) rats. This increased carotid arterial MMP2 transcription, translation, and activation, as well as transforming growth factor-␤1 activity and collagen deposition. A higher Ang II concentration, which increased arterial pressure to that of old (30 months old) untreated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
249
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(285 citation statements)
references
References 54 publications
16
249
0
2
Order By: Relevance
“…aneurysm), VR has been studied in various species including rats, rabbits, nonhuman primates, and humans, being an evolutionarily conserved process (see Table 3). The findings obtained have provided insights into the molecular and cellular mechanisms of aorta aging in humans [51][52][53][54][55][56][57][58][59][60]. Precisely, it has been shown that age-associated aorta VR is the result of a sterile inflammation, probably mediated by two supposed mechanisms: 1) infiltration of immune cells, that degrade tissues and release reactive or toxic molecules, causing DAMPs production [61]; 2) phenotypic changes in endothelial cells (ECs) and VSMCs evoked by altered and overload expression of stress and stretch signaling pathways, triggered by different stressors or damage tissue stimuli throughout life (i.e.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 93%
“…aneurysm), VR has been studied in various species including rats, rabbits, nonhuman primates, and humans, being an evolutionarily conserved process (see Table 3). The findings obtained have provided insights into the molecular and cellular mechanisms of aorta aging in humans [51][52][53][54][55][56][57][58][59][60]. Precisely, it has been shown that age-associated aorta VR is the result of a sterile inflammation, probably mediated by two supposed mechanisms: 1) infiltration of immune cells, that degrade tissues and release reactive or toxic molecules, causing DAMPs production [61]; 2) phenotypic changes in endothelial cells (ECs) and VSMCs evoked by altered and overload expression of stress and stretch signaling pathways, triggered by different stressors or damage tissue stimuli throughout life (i.e.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 93%
“…[3][4][5][6] With advancing age, TGF-␤1, collagen, and FN increase within the arterial wall, predominantly within the intimal and adventitial layers, and are linked to the ageassociated increase in arterial stiffness. 1,2,[7][8][9] Subsequently, age-associated cross-linking of collagen attributable to nonenzymatic glycation/glycosylation reactions leads to a further loss of elasticity and increased stiffness. 10 The modifications of matrix proteins alter the niche of resident vascular cells, such as vascular endothelial cells (ECs) and vascular smooth muscle cells (VSMCs), and their survival, migration, and proliferation capabilities.…”
mentioning
confidence: 99%
“…VSMC phenotypes can exhibit plasticity in response to modulation by the age‐associated alterations in the proinflammatory niche, characterized by a loss of contractility and abnormal proliferation and migration 7, 9, 27. These VSMC phenotypic shifts are driven by a coordinated repression/activation of contractile markers SM22α, α‐SMA, and myocardin 28, 29.…”
Section: Resultsmentioning
confidence: 99%
“…Zymography was performed according to modified protocols, as previously reported 5, 6, 7, 18. Sodium dodecyl sulfate polyacrylamide gel electrophoresis zymography was performed according to the manufacturer's protocol (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation